Src family kinases-mediated negative regulation of sperm acrosome reaction in chickens (Gallus gallus domesticus) - Priyadarshana, Chathura; Setiawan, Rangga; Tajima, Atsushi; Asano, Atsushi (PLOS ONE, 2020)
The acrosome reaction (AR) is a strictly-regulated, synchronous exocytosis that is required for sperm to penetrate ova. This all-or-nothing process occurs only once in the sperm lifecycle through a sequence of signaling pathways. Spontaneous, premature AR therefore compromises fertilization potential. Although protein kinase A (PKA) pathways play a central role in AR across species, the signaling network used for AR induction is poorly understood in birds. Mechanistic studies of mammalian sperm AR demonstrate that PKA activity is downstreamly regulated by Src family kinases (SFKs). Using SFK inhibitors, our study shows that in chicken sperm, SFKs play a role in the regulation of PKA activity and spontaneous AR without affecting motility. Furthermore, we examined the nature of SFK phosphorylation using PKA and protein tyrosine phosphatase inhibitors, which demonstrated that unlike in mammals, SFK phosphorylation in birds does not occur downstream of PKA and is primarily regulated by calcium-dependent tyrosine phosphatase activity. Functional characterization of SFKs in chicken sperm showed that SFK activation modulates the membrane potential and plays a role in inhibiting spontaneous AR. Employing biochemical isolation, we also found that membrane rafts are involved in the regulation of SFK phosphorylation. This study demonstrates a unique mechanism for regulating AR induction inherent to avian sperm that ensure fertilization potential despite prolonged storage.